Energy in ecosystems. - Kent, Peter; Garner, Simon; Lovering, Matthew; Video Education Australia (Bendigo, Vic. Video Education Australia, 2002)
Explores energy flow through ecosystems and how organisms at various levels in the food chain obtain their energy, use it, lose it, and store it. Number, biomass and energy pyramids are introduced with a focus on the decreasing amounts of energy available to organisms at higher trophic levels. The concepts of niche, niche overlap, competition, and limitations on organisms, are also introduced.
Writer, Simon Garner ; camera, Leigh Tilson, Matthew Lovering ; producer, Matthew Lovering ; executive producer, Mark AcAuliffe.
Narrator: Peter Kent
DVD-R (may not be compatible with all DVD players).
Keywords: Bioenergetics; Biotic communities